Analisis Implementasi IEEE 802.11ac pada Jaringan Wireless Backhaul Distribusi Provider Zettalink - Huriyati Anisa, Lila; Maria, Popy; Yusnita, Sri; Lisyadi Oktapianus, Yoppi (ELECTRON Jurnal Ilmiah Teknik Elektro, 2024)
This study aims to design, calculate the Power Link Budget, and analyze the implementation of a Broadband Wireless Backhaul network based on 802.11ac. The increasing demand for fast and stable internet access drives telecommunications service providers to continually improve their infrastructure. The Broadband Wireless Backhaul technology based on the IEEE 802.11ac standard offers a solution with high capacity, low interference, and wide coverage, making it ideal for rural areas such as Lembah Gumanti District, which faces challenges in developing telecommunications infrastructure. This study aims to design, calculate the Power Link Budget, and analyze the implementation of a Broadband Wireless Backhaul network based on 802.11ac on the Zettalink provider network in Lembah Gumanti District. The research methods include network design using UISP Design software, installation and configuration of devices, and data measurement and analysis. The network design uses Rocket Prism 5AC Gen2 radios, with Power Link Budget calculations showing a Free Space Loss (FSL) of 121.68 dB and a Received Signal Level (RSL) of -49.68 dBm. These results are consistent with measurements using UISP Design software. Comparative analysis shows significant conformity between the calculated and measured results, with an RSL measurement of -49 dBm and throughput capacity ranging from a minimum of 480 Mbps to a maximum of 655.20 Mbps. The study's results indicate that the designed network can meet the local community's internet access needs by improving connection quality and stability